Numerical modeling of interfacial heat and mass transport phenomena during a phase change using ANSYS-Fluent. (2nd October 2016) - Perez-Raya, Isaac; Kandlikar, Satish G.
ABSTRACT: Numerical modeling of phase change requires accurate estimations of heat and mass transport at the interface. The present work develops a model in ANSYS-Fluent with user-defined functions to address phase change with a planar interface. An interface boundary method determines the heat fluxes with the exact location of the interface without interpolation functions. Five cases are analyzed based on the classic Stefan problem for validating the model. The numerical model is validated against closed form theoretical solutions with agreement within 0.55%. This work can be extended to include curvature effects and the interaction between the interface and heterogeneous surfaces.